Pengaruh Lama Penyimpanan Terhadap Kualitas Semen Babi Duroc Yang Ditambahkan Pengencer Air Buah Lontar dan Kuning Telur - Usfinit, Maria Graciana; Kolo, Yulianana; Yuneriati Beyleto, Veronika (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2025)
This study aims to determine the length of storage on the quality of semen of Duroc pigs added to diluents of palm fruit water and egg yolk. This research was conducted in the laboratory of the Faculty of Agriculture, Science and Health, University of Timor, in March 2024. Semen used is fresh semen from duroc pig males aged 1 year and 7 months with healthy conditions. The method used is an experimental method using a completely randomized design (CRD) consisting of 4 treatments and 5 replicates. Each treatment is R1: Fresh semen + 15% palm fruit water + 10% egg yolk, R2: Fresh semen + 15% palm fruit water + 10% egg yolk, R3: Fresh semen + palm fruit water 15% + Egg Yolk 10% and R4: Fresh semen + palm fruit water 15% + egg yolk 10%. The variables measured were Individual Motility, Spermatozoa Viability and pH. The data obtained were analyzed using Analysis of Variance Duncan test. by using statistical software packge for the social sciences (SPSS. 20) The results of statistical research showed that the average viability of spermatozoa in treatment R1 (100.00%), R2 (99.4%), R3 (98.3%), and R4 (84.7%). Motility of individual spermatozoa R1(90.00%), R2(88.00%), R3(82.00%) and R4(80.00). pH of semen R1(7.00), R2(7.00) R3(7.00) and R4(7.00). It can be concluded that the use of Lontar Fruit Water and Egg Yolk diluents can maintain the quality of duroc pig semen.